2004
DOI: 10.2174/1566524043479185
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Influences on Ischemic Neuronal Death

Abstract: Glutamate excitotoxicity, oxidative stress, and acidosis are primary mediators of neuronal death during ischemia and reperfusion. Astrocytes influence these processes in several ways. Glutamate uptake by astrocytes normally prevents excitotoxic glutamate elevations in brain extracellular space, and this process appears to be a critical determinant of neuronal survival in the ischemic penumbra. Conversely, glutamate efflux from astrocytes by reversal of glutamate uptake, volume sensitive organic ion channels, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
297
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(308 citation statements)
references
References 0 publications
6
297
0
5
Order By: Relevance
“…Slit's ability to protect against neuronal injury in this model, the first demonstration of its kind that we are aware of, must result from Slit-mediated signaling of cytoprotective pathways in glia and/or neurons independent of any reduction in leukocyte chemotaxis. Although further studies are required to elucidate the mechanistic basis for the observed protective effect, a direct effect of Slit that improves the glial response to ischemia is possible, since the ability of glial cells to promote neuronal viability in the setting of ischemia is well established (Lee et al, 2004;Rosenberg et al, 1989;Heidinger et al, 1999;Trendelenburg et al, 2005;Swanson et al, 2004). In Drosophila, glial Slit receptors play an important role in neuron-glia interactions by influencing the survival and migration of both cell types; moreover, interfering with these interactions alters their responsiveness to Slit-Robo signaling (Kinrade et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Slit's ability to protect against neuronal injury in this model, the first demonstration of its kind that we are aware of, must result from Slit-mediated signaling of cytoprotective pathways in glia and/or neurons independent of any reduction in leukocyte chemotaxis. Although further studies are required to elucidate the mechanistic basis for the observed protective effect, a direct effect of Slit that improves the glial response to ischemia is possible, since the ability of glial cells to promote neuronal viability in the setting of ischemia is well established (Lee et al, 2004;Rosenberg et al, 1989;Heidinger et al, 1999;Trendelenburg et al, 2005;Swanson et al, 2004). In Drosophila, glial Slit receptors play an important role in neuron-glia interactions by influencing the survival and migration of both cell types; moreover, interfering with these interactions alters their responsiveness to Slit-Robo signaling (Kinrade et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are the major glial subtype and are important effectors that participate in the pathogenesis of numerous neural disorders (Miller, 2005), including trauma (Norton, 1999), stroke (Swanson et al, 2004), aging (Luo and Roth, 2000), and developmental, genetic, idiopathic or acquired neurodegenerative diseases (Abraham, 2001;Teismann et al, 2003;Barbeito et al, 2004) Modulating the behaviors of reactive astrocytes is increasingly thought to be a therapeutic strategy for the treatment of CNS disorders (Tacconi, 1998;Neufeld et al, 1999;Mrak and Griffin, 2001;Wyss-Coray and Mucke, 2002;Neufeld and Liu, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of ischemic brain damage have focused on neurons, but in recent years it has become clear that astrocytes are also damaged in ischemia (Petito et al, 1998;Liu et al, 1999;Dugan and KimHan, 2004;Swanson et al, 2004). There is evidence in vitro that oxidative stress can induce an MPT in astrocytes (Muyderman et al, 2004), however the role of Ca 2+ in MPT in astrocytes is less clear.…”
Section: Introductionmentioning
confidence: 99%